Strengthening Students' Technopreneurship Competencies through International Higher Education Best Practices - Gentur Priguna Suwarto; Iman Subasman; Agus Jamaluddin; Unang Nuansah; Fahmi Syahidi; Sukron; Adlan Khoerul (Journal of Education Research, 2026)
Digital transformation driven by Industry 4.0 compels higher education institutions to evolve into innovation ecosystems capable of developing students' technopreneurship competencies. However, significant disparities persist across institutions in cultivating such competencies. This study aims to examine international best practices in technopreneurship development within leading higher education systems and formulate strategic recommendations for Indonesian universities. A qualitative benchmarking design was employed using a literature-based approach, drawing on peer-reviewed international articles, OECD, UNESCO, and World Bank reports, and higher education policy documents from selected countries. Data were analysed through thematic synthesis and comparative analysis. Findings indicate that successful technopreneurship development is consistently supported by curricular integration of technological literacy, sustained innovation culture, strong university–industry collaboration, conducive startup ecosystems, and innovation-oriented institutional leadership. Indonesian higher education institutions should adopt a comprehensive educational framework integrating technological capability, entrepreneurial competence, and ethical leadership to prepare adaptive and globally competitive graduates for the Industry 4.0 and Society 5.0 era.